Plano de comunicação para o Kapela Bar - Thompson, Jhessyca da Costa (Brasil, 2021)
The communication between organizations and their publics changed after the progress of new technologies. What before was just information passed through companies to their publics became an intimate conversation, a close relationship whose purpose is to hear and dialogue with the consumer in order to understand their necessities. To deal with all those changes provided by technology, organizations need to know their publics to have a position on the market with a good image and reputation. The strategic planning performed by a public relations professional is the first step to outline the company's communication goals and directions, also, set mid and long-term actions to reach those objectives. Therefore, the goal of this research is to investigate the public relations by a strategic perspective to develop a communication plan to Kapela Bar. This is an applied nature, exploratory, descriptive research made by a qualitative approach. A bibliographic survey and a case study, with an application of a documental research and half-structured interviews, were executed to develop the communication plan to Kapela Bar. The planning proposed in this research allowed the understanding of Kapela’s scenario. The research and diagnosis clarified the company's challenges, also, indicated their strengths and weaknesses to build the branding of the company and to connect even more their public with the organization.